Efficacy and Safety of a Chinese Herbal Formula (Invigorating Kidney and Strengthening Spleen) in Chronic Hepatitis B Virus Carrier: Results from a Multicenter, Randomized, Double-Blind, and Placebo-Controlled Trial. (10th July 2013) - He, Jinsong; Zhou, Daqiao; Tong, Guangdong; Xing, Yufeng; Chen, Yingjie; Zhang, Xiaohui; Zhan, Bolin; Gao, Hui; Zhou, Xiaozhou; Xiong, Yiqun; Liu, Xinliang; Peng, Lisheng; et al.
Abstract : A Chinese Herbal Formula (CHF) has acquired a certain therapeutic effect on chronic HBV infection. To assess the efficacy and safety of CHF on HBV replication in chronic HBV carriers, we performed a randomized, double-blind, and placebo-controlled trial involving patients from 16 centers. A total of 300 confirmed chronic HBV carriers were randomized at baseline in a ratio of 2 : 1 to receive either CHF or placebo for 52 weeks. The results showed that a greater proportion of CHF than placebo treated patients achieved virological response at week 52; the mean decline of serum HBsAg levels in the CHF group dropped more obviously than that in the control group at all stages of the treatment; however, the rates of HBeAg loss and seroconversion had no difference between the two groups. Meanwhile, were presented significant increases in IFN- γ ; IL-2 levels and reductions in IL-4 and IL-10 levels in the treatment group compared to the control group at week 52. There were no drug-related serious adverse events. In conclusion, the treatment with 52-week CHF is safe and effective in inhibiting HBV replication in chronic HBV carriers. The ability of the compound to modulate host immune function probably contributed to this effect.